PROSTHETIC ACTIVE HAND DESIGN - Hammam, Syaiful
Cheap, moving prosthetic arms are still difficult to get in Indonesia. The frequency of amputation due to work accidents, traffic accidents, and the like is increasing, but the availability of prosthetic arms isn’t. Meanwhile they can help daily activities for users who is disabled, but they are difficult to come by at an affordable prices. Those who need prosthetic arms are the physically disabled, the majority of which are middle-lower class economies. Being physically disabled, those who are not mentally prepared and lacked in religious understanding may experience depression, helplessness. Some of them can do things like becoming a beggar, or even worse, commiting suicide. The prosthetic arm proposed here is made to cover for the lost hand and also to help doing daily activities, in order for the user to not become dependant on other people. The method used prior to design process is field survey, literature study, and analysis. The purpose of this study is to get the best solution for middle - lower economic prosthetics,. Prosthetic arms which can be used for their daily activities are needed to make user more independent and move again. But, the difference in routine for each user often limits the prosthetic arm functionality. In order to overcome that problem, a multifunctional or a modular prosthetic arm must be made according to its routine’s needs, but still aesthetically valuable. From the large number of people with physical disabilities, the high cost of prosthetic aids, and the lack of local industries that make fake hands with functions for daily activities become opportunities to provide alternative products for local industries, namely making prosthetic aids at low prices with good quality materials. easy to get and affordable. In addition, the motion system is one of the main keys of a good prosthetic product, for which a mechanical work system without electricity on a prosthetic is chosen so that the working system is good but affordable in terms of price. For this reason, an active prosthetic arm made of PVC pipe is made with a modular system to help disabled people carry out activities.